2014
DOI: 10.1002/ente.201402005
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Energy Production of Dye‐Sensitized Solar Cell Modules for Building‐Integrated Photovoltaic Applications

Abstract: The standard parameters considered to compare energy-harvesting efficiency such as the efficiency measured in standard test conditions or the concept of peak Watt power production may lead to an incorrect estimation of the real producible energy. In this work, we aim to confirm that in realistic outdoor building-integrated photovoltaic (BIPV) installations, the gap between dye-sensitized solar cells (DSC) and other available technologies is lower than expected in terms of producible energy. We have developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Performance depends on the modules response to spectral, reflection, temperature, irradiance, and nominal power variations occurring throughout the day and the seasons [14]. It is thus important also to consider not only the total energy produced outdoors by different panels over the course of a time period [20,21] but also how the performance varies and responds to different parameters in varying operating conditions, including indoors.…”
Section: Introductionmentioning
confidence: 99%
“…Performance depends on the modules response to spectral, reflection, temperature, irradiance, and nominal power variations occurring throughout the day and the seasons [14]. It is thus important also to consider not only the total energy produced outdoors by different panels over the course of a time period [20,21] but also how the performance varies and responds to different parameters in varying operating conditions, including indoors.…”
Section: Introductionmentioning
confidence: 99%
“…[37]. The framework could hence be adapted to investigate building facade area as well as roof space to consider how much PV could be installed in the future [38]. More broadly the methodology would be useful to consider other energy technologies, such as combined heat and power (CHP) which can also be applied at domestic and non-domestic building scale and at a district-level.…”
Section: Discussionmentioning
confidence: 99%
“…They evidenced how DSM performs better than thin film even if its use does not provide the necessary saving improvement to reach NZEB conditions for the climate considered. Reale et al [28] developed a model of DSM using data coming from outdoor conditions to estimate producible energy of DSM with respect to the well-established technologies for a generic STPV installation. They concluded that DSM should have an equivalent efficiency in real outdoor conditions that is 16% higher than the one at standard test conditions in the laboratory (3.36%).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recent attempts, few studies in the literature regard the evaluation of thermal and electrical properties of DSM for STPV [29], especially in real operating conditions [28,30]. This lack of data does not allow reliable evaluation of DSM potential of energy saving in buildings.…”
Section: Introductionmentioning
confidence: 99%